Psychometric evaluation of the Behavioral Activation for Depression Scale-Short Form in Alzheimer's caregivers. (2nd September 2021) - Bos, Taylor; Malcarne, Vanessa L.; Grant, Igor; Mausbach, Brent
Abstract: The present study evaluated the psychometric properties of scores from the Behavioral Activation for Depression Scale Short Form (BADS-SF) in a sample of older age, spousal, Alzheimer's caregivers participating in an evaluation of Behavioral Activation (BA) therapy compared to an Information Support (IS) group. At baseline assessment, caregivers ( N = 170) completed the BADS-SF, which is comprised of two subscales (Activation and Avoidance) that can be summed to produce a total score. Confirmatory factor analysis was used to evaluate structural validity. A two-factor solution fit the data adequately; however, the first item on the scale did not load onto either factor. Internal consistency reliability for the total and subscales scores was poor as measured by Cronbach's alpha. Construct validity was evidenced by significant expected relationships with depression. Pre- to post-intervention scores did not evidence sensitivity to change. These findings provide some support but raise important concerns about the validity and reliability of BADS-SF scores in a population of older adult caregivers.